SCIENTIFIC APPROACHES TO PROFESSIONAL COMPETENCES DEVELOPMENT OF FUTURE SOFTWARE ENGINEERS DESCRIBED IN THE LOCAL AND FOREIGN LITERATURE - Kontsedailo V. (Kherson State University, 2017)
This article deals with scientific approaches to professional competencies development of future software engineers, described in the local and foreign literature. It was found, that software development process usually occurs in the context of software project management. According to various papers, the major challenge in the area of software project management is the high failure rate of software development projects. One of the main factors contributing to the failure of software development projects is that people, involved in the process, including software engineers, do not possess certain soft competencies, essential to the project success. Conducted a literature review of studies, published on the topic of professional competencies development of future software engineers. Found that for now there are plenty of papers on and scientific approaches to professional soft competencies development of future software engineers. As per the analysis in the article, present scientific approaches can be divided into three groups: ones, based on the correspondent extracurricular activities; ones, based on project-oriented learning, and ones, based on the use of Information and Communication Technologies, for example, game simulators in combination with lectures and educational projects. The above-mentioned groups of approaches are described in more details, broken down by papers of particular authors.